Dimensi Ketenagakerjaan Pada Prinsip Tanggung Jawab Sosial Perusahaan - Aryo Damar (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda Palembang, 2025)
Corporate social responsibility (CSR) is a company's commitment to contribute to sustainable development by taking into account social, economic and environmental welfare. One of the important dimensions in the implementation of CSR is employment, which includes aspects of protecting workers' rights, welfare, fairness in employment opportunities, and improving the quality of human resources. This study aims to analyze how CSR principles are implemented in the employment dimension, as well as its impact on workers' welfare and company productivity. Using a qualitative approach and literature study, the results show that the application of CSR principles in employment can improve harmonious industrial relations, reduce the level of social inequality, and improve the competitiveness of companies through sustainable employment policies. Therefore, the integration of labor aspects in CSR policies is an important strategy for companies in achieving business sustainability and creating positive social impacts.